Patient perspectives of jail based MOUD treatment: views of individuals who have returned to the community following incarceration - Claudia Santelices; Warren Ferguson; Rebecca Rottapel; Ekaterina Pivovarova; Elizabeth Evans; Thomas Stopka; Peter Friedmann (Health & Justice)
Abstract Background Massachusetts passed legislation in 2018 to mandate provision of medications for opioid use disorder (MOUD) in select jails to address the high risk of opioid overdose after release. Since 2019, we have conducted a Type-1 hybrid effectiveness-implementation study of this program. We present findings on the perspectives and experiences of persons treated in these jails. Methods We conducted qualitative analyses of semi-structured interviews that were conducted in 2022 with 38 adults released to the community who had been treated with MOUD while living in one of eight Massachusetts jails. The Exploration, Preparation, Implementation, and Sustainment (EPIS) framework informed development of the interview guide and analysis of qualitative data. Deductive and inductive strategies were used for coding and analyses. Results Participants were 41.5 years old; predominantly male; 84.2% white, 23.7% Hispanic/Latino and 7.9% Black; and most continued taking MOUD. Thematic analysis focused on four code reports: Perception of Addiction/MOUD, Barriers/Facilitators, Impact of MOUD in Jails, and Stigma. Participants perceived that MOUD helped to prevent relapse. Prompt and consistent access to medication, and respectful treatment by healthcare and carceral staff were highlighted as facilitators. In contrast, some participants perceived that policy-centered rather than patient-centered treatment drove timing of medication initiation or response to medication changes. Insufficient staffing and the COVID-19 pandemic contributed to treatment delays. Overall, individuals incarcerated in jails that have expanded treatment eligibility to include earlier induction with MOUD generally felt more positive about their experience than individuals reporting delayed induction. Conclusions Participants valued the ability of jail based MOUD programs to help clients achieve recovery from OUD. Their perceptions highlight the intrinsic value of MOUD programs that promote and support wellbeing through a person-centered approach to treatment. Participants stressed that MOUD programs should be patient-centered and guided by patients’ symptoms and needs.